Targeting Innate-Like T Cells in Tuberculosis - Huang, Shouxiong (Frontiers in Immunology, 2016)
Peptide-specific conventional T cells have been major targets for designing most anti-mycobacterial vaccines. Immune responses mediated by conventional T cells exhibit a delayed onset upon primary infection and are highly variable in different human populations. In contrast, innate-like T cells quickly respond to pathogens and display effector functions without undergoing extensive clonal expansion. Specifically, the activation of innate-like T cells depends on the promiscuous interaction of highly conserved antigen-presenting molecules, non-peptidic antigens, and likely semi-invariant T cell receptors. In anti-microbial immune responses, mucosal-associated invariant T (MAIT) cells are activated by riboflavin precursor metabolites presented by MHC-related protein I (MR1), while lipid-specific T cells including natural killer T (NKT) cells are activated by lipid metabolites presented by CD1 proteins. Multiple innate-like T cell subsets have been shown to be protective or responsive in mycobacterial infections. Through rapid cytokine secretion and effector response, innate-like T cells function in early defense and memory response, offering novel advantages over conventional T cells in the design of anti-tuberculosis strategies.